Management accounting - Swain, Monte R. (Thomson/South-Western, 2005)
Accounting is about decision making using financial information. The text focuses on developing a student's the ability to critically analyze accounting information and make informed business decisions. Students are exposed to a lot of real-world examples where they can see the effect that accounting information has on the decisions made by real companies. Also chapters are split into basic and expanded material so that the professor can easily cover the basics of a topic or, if he or she prefers, delve deeper into a selected topic. Finally, analysis is incorporated throughout the text so that students can learn to use accounting information as they learn how that information is prepared